Microbial Profile of Frozen Fisheries Products at UPT PMP2KP Surabaya - Fadiya Furuujihim Rohsarifuddin; Yolandha Sephiani Nurhafifah; Puspa Maharani; Kismiyati Kismiyati; Rahmah Hendriyati; Woro Hastuti Satyantini (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2025)
ABSTRACTMicrobial contamination of food products is one of the significant hazards in food safety because the nature of food-polluting bacteria is generally pathogenic.This research was conducted at the Microbiology Laboratorium in UPT PMP2KP Surabaya. Samples tested in this research including frozen fish, frozen shrimp, and frozen value added products with microbiological parameters tested are Total Plate Count, Salmonella, and Escherichia coli. The results obtained in this research showed that 100% of 21 frozen fish and shrimp samples met SNI safety standards, namely 1 x 105 CFU/g for TPC, 3 MPN / g for E. coli, and negative for Salmonella.Keywords: E. coli, Food Safety, Frozen Fisheries Product, Salmonella